China's export performance and shifting comparative advantage - Yang, Minhua (2008)
The motivation for this thesis is to fill up the empirical gaps in the area of comparative advantages of China's exports. This study undertakes a detailed analysis of China's export performance and shifting export specialization in the U.S. market over the period of 1980-1999 and then links this analysis to the sources of China's comparative advantage. China's relative maturity as an exporter is analyzed with the application of Balassa's revealed comparative advantage (RCA) indices at the Standard International Trade Classification (SITC) two and three-digit product category level.